Synthesis, Anti-Inflammatory and Anti- Nociceptive Activities and Cytotoxic Effect of Novel Thiazolidin-4-ones Derivatives as Selective Cyclooxygenase (COX-2) Inhibitors - Seyed Adel Moallem (Iranian Journal of Basic Medical Sciences, 2013)
Objective(s): Nowadays, COX- 2 inhibitors such as valdecoxib are removed from the market because of their cardiovascular toxicity and their potential to increase the risk of strokes. In response to this, medicinal chemists have attempted to synthesize new classes of COX-2 Inhibitors.